Transformative Praxis Beyond Methodology: A Multi-Theoretical Integration of Classroom Action Research for Novice Educators' Critical Reflection and Epistemic Awakening - Yulia Afrilliana; Eko Purnomo; Rasmi Hi Panu; Eka Ismaya Indra Purnamanita; Arifatul Ma’ani; Siti Amaliati (Tarqabin Nusantara Group, 2026)
Introduction: Critical reflection constitutes a foundational competency for novice educators, yet remains suboptimally developed due to limited experiential scaffolding and insufficient systematic guidance. While Classroom Action Research (CAR) has been widely employed as a methodological tool, its transformative potential as a multi-theoretical praxis remains underexplored. This study addresses this gap by integrating four complementary theoretical frameworks—Dewey's reflective thinking, Korthagen's ALACT model, Mezirow's transformative learning, and Freirean critical pedagogy—to reconceptualize CAR not merely as research methodology but as transformative praxis capable of catalyzing epistemic awakening among novice educators. Method: Employing a participatory action research design, this study conducted an intensive one-day workshop with novice educators (pre-certification teachers) in the coastal communities of Sidoarjo Regency, Indonesia. The intervention comprised four sequential phases: (1) conceptual grounding through theoretical orientation, (2) problem identification and critical analysis using classroom data as evidentiary foundations, (3) CAR proposal development with peer review and mentor feedback, and (4) evaluation and reflective synthesis. Data were collected through pre-post evaluation forms, Result: Evaluation data revealed significant paradigmatic shifts in participants' understanding of critical reflection and CAR. Participants transcended viewing reflection as administrative ritual, instead embracing it as transformative strategy for cultivating sustained critical consciousness. Conclusion: This study contributes theoretical novelty by demonstrating the integrative power of synthesizing Deweyan, Korthagenian, Mezirowian, and Freirean perspectives within a unified framework for novice educator development. The findings validate CAR's function not merely as methodological instrument but as transformative praxis that catalyzes epistemic awakening and perspective transformation.